PENGARUH DIMENSI FRAUD DIAMOND DAN RELIGIUSITAS TERHADAP KECURANGAN AKADEMIK - Ni Putu Ayu Yuniari; Sang Ayu Putu Arie Indraswarawati; Cok. Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of diamond fraud and religiosity on academic fraud in accounting students of the University of Hindu Indonesia . This research was conducted at the University of Hindu Indonesia. The number of samples taken was 172 students with a probability sampling method. Data collection was carried out by distributing questionnaires. The analysis technique used is multiple linear regression. The results showed that pressure has a significant effect on academic fraud y ang means that the pressure received by students triggers students to commit academic fraud. Ability has a significant effect on academic fraud, which means that the higher the student's ability to commit cheating, the higher the cheating is committed. Religiosity has a significant effect on academic fraud, which means that the higher the level of religiosity, the more students understand that in religion there is a punishment in the hereafter for doing bad things. Opportunity and rationalization do not have a significant effect, which means that opportunity and rationalization do not influence students to commit academic fraud.